1994
DOI: 10.1016/0147-9571(94)90038-8
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune status of coronavirus-infected neonatal calves

Abstract: A preliminary study was conducted to determine the cellular immune status of neonatal, colostrum-deprived calves following inoculation with either attenuated or virulent bovine coronavirus (BCV). Uninfected calves served as controls. To determine the intestinal and systemic cellular immune status, we performed MHC-restricted cytotoxic lymphocyte (CTL) assay on mesenteric lymphocytes, enumerated T cell subsets in peripheral blood lymphocytes, and examined histopathological alterations in mesenteric lymph nodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Additionally, this may be because of a lack of a cell-mediated immune response to BCoV infection. Currently, data on T-cell immunity in relation to BCoV infection are scant [ 58 ]. Thus, further studies are necessary to elucidate the appropriate immune response that can prevent viral replication, shedding, and transmission during BCoV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this may be because of a lack of a cell-mediated immune response to BCoV infection. Currently, data on T-cell immunity in relation to BCoV infection are scant [ 58 ]. Thus, further studies are necessary to elucidate the appropriate immune response that can prevent viral replication, shedding, and transmission during BCoV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, all three viruses belong to families known to possess immunosuppressive abilities in other species of animals (Notkins et al 1970, Mims 1986, Kapil et al 1994. Therefore, these viruses may interfere with research.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, CD147 seems to be hyper-expressed in CD3+ T lymphocytes of SLE individuals compared to healthy controls, predisposing these patients to SARS-CoV-2 cytopathic effect on white blood cells[ 80 ]. Although the role of SARS-CoV-2 in human secondary and tertiary lymphoid organs is unclear, it has been shown that a virulent strain of bovine CoV may induce depletion of T cells in calf Peyer's patches and mesenteric lymph nodes[ 81 ]. In SARS-CoV-2 infected people, lymphopenia especially affects T and NK lymphocyte populations and memory cells[ 27 ].…”
Section: The Immune Response Against Sars-cov-2mentioning
confidence: 99%